Recent progress in high-entropy metallic glasses - Luan, Hengwei; Li, Keran; Shi, Lingxiang; Zhao, Wei; Bu, Hengtong; Gong, Pan; Yao, Ke-Fu (Journal of materials science & technology, 2023)
•The ΔH-δ regions of the HEMGs with low, medium and high glass-forming abilities are proposed.•The reported mechanical and magnetic properties of the HEMGs are summarized and discussed.•The thermal stability, mechanical and functional properties of HEMGs are presented, and the advantages and disadvantages of HEMGs are discussed. High-entropy metallic glass (HEMG) is a new type of metallic material with high-entropy alloy-like composition and amorphous structure, which render HEMGs unusual glass formation behaviors and unique properties. In recent years, fast research progress has been witnessed on the HEMGs, and thus a systematic review is required. In this review, we first introduce the concept of the HEMGs and summarize the developed HEMGs. Then, the glass-forming ability of the HEMGs is discussed, and the general rules are proposed. Focusing on the thermal stability of HEMGs, the effect of entropy on the energy states of HEMGs and the crystallization behavior of HEMGs are discussed. Finally, the mechanical, magnetic, catalytic and other properties of HEMGs are presented, and the advantages and disadvantages of HEMGs are shown. This review can function as a quick guideline for overviewing the HEMG field. [Display omitted]